Re-existências de mulheres no território agroextrativista Pirocaba, Baixo Tocantins, Pará: por uma comunicação agroecológica, feminista e popular - REIS, Tatiana Nazaré Amaral Ferreira (Universidade Federal do Pará, 2025)
Women from the Pirocaba Agroextractivist Territory, in Abaetetuba, in the Baixo Tocantins region, actively participate in resistance movements against the installation of the Private Use Terminal by the Cargill global trader, aimed at accelerating the export of commodities, mainly soybeans and corn. Women from Pirocaba dedicate themselves to working in activities such as agroecological agriculture, extractivism, craftwork and fishing, recording production in Agroecological Logbooks, instruments based on feminist economics, aimed at valuing women's work and production. It is argued that the use of Logbooks since 2018 has encouraged the productive and socio-territorial organization of Pirocaba, among other benefits. This thesis adopts action research as its main methodology in order to understand how counter-hegemonic communication, which opposes the hegemony of large media corporations, can strengthen Pirocaba women's resistance by promoting visibility of their Amazonian ways of life and the feminist and popular economy that they practice. In the first stage of the research, the potential of Agroecological Logbooks was investigated to support territorialized communication processes facing the challenges experienced by women of the Pirocaba territory. In the second stage, we proceeded to understand how large enterprises, especially Cargill's Private Use Terminal project in Abaetetuba, use “community relations” tools to defend their hegemonic interests. In the final stage of the research, conversation circles and communication workshops were put into practice with a group of women from the territory, resulting in the creation of the Vozes do Pirocaba podcast, an instrument of agroecological, feminist and popular territorial based communication carried out in a participatory manner throughout its design and distribution process.